Genetic differentiation between subpopulations of Swedish mountain (Fjäll and Fjällnära) cattle - Johansson, Anna Maria; Upadhyay, Maulik; Strandberg, Erling; Eriksson, Susanne (2020)
The Swedish Mountain (Fjall) cattle and the subpopulation Fjallnara originates from northern Sweden. They are differentiated from both traditional and commercial cattle from southern Sweden. We analysed data from the GGP HD150k SNP array and investigated genetic diversity and differences between Fjall and Fjallnara, and between different groups of Fjallnara. We found that the Fjallnara can be divided into four groups, which are differentiated from each other and from the other Fjall cattle. We also compared allele frequencies between different groups of Fjall and Fjallnara for some of the functional SNPs included in the SNP array. Interestingly, the B allele of Beta lactoglobulin has a very high frequency (94%) in the Fjallnara cattle, which is significantly different from the frequency in the Fjall cattle (60%). Comparing older samples of Fjall cattle with more recent samples, we found a significant increase in the frequency of the B allele in Fjall cattle.